Uneven Gains, Rising Constraints: Assessing the U.S.–China Trade War’s Effects on ASEAN and Indonesia - Didi Rahmadi; Lara Indah Yandri (LPPM Universitas Muhammadiyah Sumatera Barat, 2025)
This paper examines how the U.S.–China trade war functions as a structural geoeconomic shock that reshapes ASEAN’s economic opportunities and strategic constraints, with particular attention to Indonesia’s policy dilemma. The study applies library research using qualitative document analysis and a narrative–thematic synthesis of academic and policy sources to trace the main transmission mechanisms (tariffs, supply-chain reallocation, technology contestation, and investor expectations). The analysis shows that ASEAN’s adjustment is inherently double-edged: trade diversion and relocation prospects coexist with deeper vulnerabilities stemming from continued reliance on China-centred production networks and the United States’ role in investment and technology. For Indonesia, the trade war expands room for selective gains but simultaneously intensifies constraints on market diversification, industrial upgrading, and strategic autonomy, implying that resilience depends on proactive capability building and coordinated regional strategies rather than reactive tariff management. As a non-SLR, document-based study, the paper cannot provide causal estimation or sector-level measurement of heterogeneous effects across ASEAN members and relies on the completeness and quality of available secondary materials.Keywords: US-China Trade War, ASEAN, Indonesia